English grammar for ESL learners - Swick, Ed Edward (Practice makes perfect, 2022)
"For clear, precise explanations of all aspects of English grammar, look no further than [this book]! As a beginning learner of English, you might find that grammar concepts can be confusing. To make progress with your English skills, you need guidance through tricky grammar areas. This book will help develop mastery. The more you practice, the more you become proficient in how you use English. [This book] will help increase your confidence in writing and communicating in English by helping you understand the different rules and elements of grammar, broaden your knowledge with sentence rewrites and creative writing prompts, build your grammar skills with more than 120 engaging exercises, [and] test your overall comprehension with a comprehensive review section"--Back cover.